Robust Trabecular Microstructure in Type 2 Diabetes Revealed by Individual Trabecula Segmentation Analysis of HR‐pQCT Images - Starr, Jessica F; Bandeira, Leonardo C; Agarwal, Sanchita; Shah, Ankit M; Nishiyama, Kyle K; Hu, Yizhong; McMahon, Donald J; Guo, X Edward; Silverberg, Shonni J; Rubin, Mishaela R (Journal of bone and mineral research, 2018)
ABSTRACT Type 2 diabetes (T2D) patients have an increased fracture risk, which may be partly explained by compromised bone microarchitecture within the cortical bone compartment. Data on trabecular bone parameters in T2D are contradictory. By high‐resolution peripheral quantitative computed tomography (HR‐pQCT), trabecular microarchitecture is preserved, yet larger trabecular holes are detected in T2D by MRI and DXA‐based trabecular bone scores are abnormal. To determine if there are differences in trabecular microstructure, connectivity, and alignment in postmenopausal women with T2D as compared with controls, we performed an individual trabecula segmentation (ITS) analysis on HR‐pQCT scans of the distal radius and tibia in 92 women with (n = 42) and without (n = 50) T2D. Unadjusted analyses showed that T2D subjects had greater total trabecular bone volume, trabecular plate volume fraction, plate number density, plate junction density, and axial alignment at the radius and tibia, and increased plate tissue fraction, but decreased rod tissue fraction and rod length at the radius (p < 0.05 for all). After adjustments for clinical covariates, plate number density and plate junction density remained higher at the radius and tibia, whereas total trabecular bone volume was increased and trabecular rod length was decreased at the radius. These differences remained significant after adjustment for hip BMD and trabecular volumetric bone density. Notably, the increased plate‐like ITS qualities were seen in those with T2D duration of <10 years, whereas ITS parameters in subjects with T2D duration ≥10 years did not differ from those of control subjects. In conclusion, postmenopausal women with early T2D had a greater plate‐like and less rod‐like trabecular network. This early advantage in trabecular plate quality does not explain the well‐established increased fracture risk in these patients and does not persist in the later stage of T2D. © 2018 American Society for Bone and Mineral Research.